Development of a Specific rsmG Gene Detection Using In House Primer Design of Mycobacterium fortuitum and Modelling Structure of 3D Protein - Pinasti, Roro Titah; Kurniawati , Siti; Makta , Averoes Gibraltar; Ramadhani , Najma; Savitry , Diaz Ayu (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
Developing specific detection methods for the rsmG gene in Mycobacterium fortuitum is crucial for improving treatment strategies. This study aimed to design and validate an in-house primer detection method for thersmG gene in Mycobacterium fortuitum. To detect the rsmG gene inMycobacterium fortuitum using DNA fragments based on the effectiveness of the in-house primer. Developing this in-house detection method also highlights the importance of local and in-house primer design for specific gene detection using bioinformatics design and structure. This approach can be applied to other genes and bacteria for further research and treatment. This method is used withbioinformatics design from the NCBI database based on the OF855_RS30840and reference sequence NZ_CP107719.1 with gene description of 16S rRNA (guanine (527) N(7) -methyltransferase. The protein model structure template is A0A2U9Q1N61. A using the SWISS-MODEL. The results have 50 - 60% of GC contents from 10 primer pairs with the melting temperature range are 59,33 - 69,46 from NCBI, have forward and reverse. The optimum pairs are the fourth pairs of primers which has optimum self complementarity and relatedness ofeach pair. The results of building model 3D protein were successfully built fromOF855_RS30840. In our conclusion, the primer was obtained and successfullyused to model the 3D structure of the protein encoded by the rsmG gene.